Acceptance level of consumers towards genetically modified food: a review / Siti Fatimah Eshak - Eshak, Siti Fatimah (Faculty of Plantation and Agrotechnology, 2018)
By the increasing in the number of commercial application and production GM food, there are ethically issues which have been controversial. Many of them claimed that the GM food are unnatural, give negative impact to the environment, and also rise of superweed. However, it also have benefit such can increase yield, have more nutritional value, reduce the production cost, increase profit and reduce pesticide usage. This paper aimed to explore the level of consumer acceptance towards GM food based on the difference type of application and country, attitude of consumer, consumer demand to be inform, labeling policies, trust in information, level of consumer knowledge and the tangible benefit that consumer get by consuming GM food. Based on this review, we know that consumer have different perception in GM food which is positive attitude will lead to the willingness to purchase GM food. Otherwise, negative attitude will lead to the rejection of GM food.